To Buy or Not to Buy from the Internet: Reasons to Behave in a Certain Manner in An International Online Commerce Society - Oana Tugulea; Claudia Bobalca (CES Working Papers, 2016)
The purpose of this research is to identify the most important reasons that drive young Romanian Internet users to buy or to avoid buying from the Internet and to investigate the differences in the reasoning between two groups of Internet users. The most important reasons to buy from the Internet, as selected by the buyers group, are aspects concerning physical and financial gains: “comfort ability” and “time saving” (easiness to place an order – physical gain) on one hand, and “advantageous price” (financial gains) on the other hand. By far, the most important reason to avoid Internet shopping, for both analysed groups was the “impossibility to touch and test the product”.
Keywords: M31; M39; 330; Internet; online shopping; reasons to buy; reasons not to buy